The Influence of Student Learning Motivation and Understanding Diagrams Using Microsoft Office Visio On Cognitive Learning Outcomes in Lessons of Software Modeling - Suci Rhamadani Setianti; Agus Efendi; Febri Liantoni (Journal of Informatics and Vocational Education, 2021)
The purpose of this study was to determine whether there is an effect of motivation and understanding of student diagrams through the use of Microsoft Visio on cognitive learning outcomes of XI RPL class students in Software Modeling subjects at SMKN 2 Surakarta. This research is an ex post facto quantitative research and the subjects in this study were 32 students of class XI RPL SMKN 2 Surakarta in one class. Data were collected using questionnaires, tests, and documentation. Test the validity of the research instrument using Product Moment correlation, and reliability testing using Cronbach's Alpha. The prerequisite analysis consisted of a normality test, a linearity test, and a multicollinearity test. Hypothesis testing consists of simple regression and multiple regression. The results showed that: 1) there was a positive and significant influence of Learning Motivation on Cognitive Learning Outcomes with rx1y = 0.455; r2x1y = 0.207; and tcount (2.282)> t table (2.093) at the 5% significance level. 2) there is a positive and significant influence of Diagram Understanding on Cognitive Learning Outcomes with rx2y = 0.669; r2x2y = 0.447; and tcount (4.020)> ttable (2.093) at the 5% significance level. 3) there is a positive and significant influence on Learning Motivation and Understanding of the Diagrams together on Cognitive Learning Outcomes with Ry (1,2) = 0.716; R2y (1,2) = 0.513; and the value of Fcount (9.990)> Ftable (3.49) at the 5% significance level.